Relationship between Exports and Economic Growth in Libya: Time Series Analysis Over the Period (1970 - 2010). - Nagem, Osama; Howaidi , Zarroug (Dirasat in Economics and Business, 2020)
The main purpose of the paper is to investigate the relationship between the exports and economic growth in Libya by examining the export-led growth (ELG) hypothesis using annual data for the period 1970-2010, Real non-oil GDP was used as a dependent variable, exports and imports, total capital accumulation and the terms of trade as independent variables. The unit root tests of Dickey Fuller and PhillipsPeron were used to test the stability of the variables, and the cointegration approach of the Autoregressive Distributed Lag through the ARDL method was used to estimate the model. The results of unit root tests showed that all variables are constant in their levels (0)I, except for the terms of trade, it was stable in its first difference (1)I. Whereas, the cointegration test confirmed a long-run, equilibrium relationship between variables. The error correction model was applied to estimate the short-run relationship and the results showed that the error correction term has a negative sign, its value is very high, and statistically, it is about -0.98, which states that 98% of the disequilibrium in the current year is corrected in the next year in each shock. Granger's causality test showed that there is a one-way relationship between exports and economic growth going from output to exports. Accordingly, the results of the study support the hypothesis that growth leads exports rather than exports driving growth in Libya. The main purpose of the paper is to investigate the relationship between the exports and economic growth in Libya by examining the export-led growth (ELG) hypothesis using annual data for the period 1970-2010, Real non-oil GDP was used as a dependent variable, exports and imports, total capital accumulation and the terms of trade as independent variables. The unit root tests of Dickey Fuller and PhillipsPeron were used to test the stability of the variables, and the cointegration approach of the Autoregressive Distributed Lag through the ARDL method was used to estimate the model. The results of unit root tests showed that all variables are constant in their levels (0)I, except for the terms of trade, it was stable in its first difference (1)I. Whereas, the cointegration test confirmed a long-run, equilibrium relationship between variables. The error correction model was applied to estimate the short-run relationship and the results showed that the error correction term has a negative sign, its value is very high, and statistically, it is about -0.98, which states that 98% of the disequilibrium in the current year is corrected in the next year in each shock. Granger's causality test showed that there is a one-way relationship between exports and economic growth going from output to exports. Accordingly, the results of the study support the hypothesis that growth leads exports rather than exports driving growth in Libya.